2007
DOI: 10.1016/j.cell.2007.03.050
|View full text |Cite
|
Sign up to set email alerts
|

RF3 Induces Ribosomal Conformational Changes Responsible for Dissociation of Class I Release Factors

Abstract: During translation termination, class II release factor RF3 binds to the ribosome to promote rapid dissociation of a class I release factor (RF) in a GTP-dependent manner. We present the crystal structure of E. coli RF3*GDP, which has a three-domain architecture strikingly similar to the structure of EF-Tu*GTP. Biochemical data on RF3 mutants show that a surface region involving domains II and III is important for distinct steps in the action cycle of RF3. Furthermore, we present a cryo-electron microscopy (cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
170
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(197 citation statements)
references
References 57 publications
(95 reference statements)
27
170
0
Order By: Relevance
“…It was demonstrated that the affinity of RF1 for the post-termination complex is much higher than that of RF2. This would immediately suggest that RF1 is more difficult to recycle than RF2, which is also evident from the measurements of the spontaneous recycling time of the two release factors under the same experimental conditions (ϳ60 s for RF1 and 11 s for RF2) (28). In line with this argument, it has also been shown that RF1 is more dependent on RF3 for its recycling than is RF2 (13,28).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It was demonstrated that the affinity of RF1 for the post-termination complex is much higher than that of RF2. This would immediately suggest that RF1 is more difficult to recycle than RF2, which is also evident from the measurements of the spontaneous recycling time of the two release factors under the same experimental conditions (ϳ60 s for RF1 and 11 s for RF2) (28). In line with this argument, it has also been shown that RF1 is more dependent on RF3 for its recycling than is RF2 (13,28).…”
Section: Discussionsupporting
confidence: 66%
“…This would immediately suggest that RF1 is more difficult to recycle than RF2, which is also evident from the measurements of the spontaneous recycling time of the two release factors under the same experimental conditions (ϳ60 s for RF1 and 11 s for RF2) (28). In line with this argument, it has also been shown that RF1 is more dependent on RF3 for its recycling than is RF2 (13,28). The slow dissociation of RF1 after peptide release can have a significant consequence in a polysomic scenario where multiple ribosomes are lined up on a translating mRNA.…”
Section: Discussionmentioning
confidence: 77%
“…1 and Fig. S3), in agreement with conclusions based on the results of numerous other approaches (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In some cases, multiconformer analysis may provide information about molecular motions that is not evident from TLS-derived B factor values alone.…”
Section: Resultssupporting
confidence: 78%
“…These two helices have been proposed to contact a common (unspecified) component of the ribosome (31). In RF3 a portion of the GЈ subdomain, including helix A GЈ , is present (32), but in IF2 the GЈ subdomain is completely missing, which suggests that these factors also may interact distinctly with L7/L12. This idea has precedent in other G proteins, which interact with GTPaseactivating proteins (GAPs) in structurally distinct ways (33).…”
Section: Discussionmentioning
confidence: 99%